Pengaruh Pendidikan Ekonomi Keluarga dan Kontrol Diri Terhadap Perilaku Ekonomi - Putri, Riva Amelia; LV, Yuhendri (Jurnal Economic Resource, 2025)
The study is intended to examine the extent to which economic behavior is influenced by family economic education or self-control in the children of dumpling entrepreneurs in Pariaman City. This research was carried out because there are still children of dumpling entrepreneurs who show irrational economic behavior. The sample consisted of 109 adolescents who were determined using the Slovin formula, random sampling was used as a sampling technique. Evaluating the data after it was collected through the distribution of questionnaires was carried out a classic assumption test. The conclusion of the study found that simultaneously the variables of family economic education and self-control had a positive and significant effect on economic behavior in the children of dumpling entrepreneurs in Pariaman City. However, the family economic education variable did not have a positive and significant effect on the economic behavior variable, only self-control had a positive and significant influence on economic behavior in dumpling business children in Pariaman City. This study highlights the role of family economics education in encouraging logical or planned economic behavior and opens space for further research into other factors currently not covered in the research paradigm.